The Impact of Human Immunodeficiency Virus (HIV) on Inflammatory Bowel Disease (IBD): A Retrospective Nationwide Study - Then, Eric; Uhlenhopp, Dustin J.; Barakat, Mohamed; John, Febin; Gayam, Vijay; Lopez, Michell; Sunkara, Tagore; Gaduputi, Vinaya (Current HIV Research, 2021)
Background: The “remission theory” is an emerging concept that suggests the presence of human immunodeficiency virus (HIV) results in decreased disease severity in patients with inflammatory bowel disease. This theory is based upon evidence that implicates CD4 T-lymphocytes in the pathogenesis of both Crohn’s disease and ulcerative colitis. This study sought to elucidate the legitimacy of this theory. Methods: A retrospective cohort analysis of all adult inpatient hospitalizations for inflammatory bowel disease (IBD) using the 2016 National Inpatient Sample (NIS) was conducted. Our study population included patients admitted with IBD who were infected with HIV. We compared our study group to patients who also had IBD but were not infected with HIV. Baseline demographic characteristics, resource utilization, and in-hospital mortality rates were extracted for both groups. Results: A total of 58,979 patients were admitted for IBD in 2016. Of those patients, we identified 145 who also had the presence of HIV. We found that patients with ulcerative colitis and HIV had a shorter length of hospital stay (4.1 vs. 5.9 days, p-value < 0.01), lower hospital charge (35,716 vs 52,893, p-value < 0.01), and lower hospital cost (7,814 vs. 13,395, p-value < 0.01) than those who did not have HIV. In patients with Crohn’s disease, the presence of HIV resulted in decreased colonoscopy rates (0% vs. 17.4%, p-value < 0.01); however, the rate of esophagogastroduodenoscopies was not statistically significant (7.1% vs. 14.7%, p-value 0.106). Conclusion: In this retrospective population-based study, we found that patients with ulcerative colitis and concurrent HIV had a milder course of the disease when compared to ulcerative colitis patients that were not infected with HIV. These findings support the remission theory in that HIV may play a role in inflammatory bowel disease.
Keywords: T-helper cell